Overview of research progress and application of experimental models of colorectal cancer - Liu, Li; Yan, Qiuying; Chen, Zihan; Wei, Xiaoman; Li, Lin; Tang, Dongxin; Tan, Jiani; Xu, Changliang; Yu, Chengtao; Lai, Yueyang; Fan, Minmin; Tao, Lihuiping; et al. (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) is the third most common malignancy in terms of global tumor incidence, and the rates of morbidity and mortality due to CRC are rising. Experimental models of CRC play a vital role in CRC research. Clinical studies aimed at investigating the evolution and mechanism underlying the formation of CRC are based on cellular and animal models with broad applications. The present review classifies the different experimental models used in CRC research, and describes the characteristics and limitations of these models by comparing the research models with the clinical symptoms. The review also discusses the future prospects of developing new experimental models of CRC.